Estudio prospectivo del proceso de reinserción en Colombia (2007)
For more than 60 years, Colombia has been suffering an internal conflict, full of a constant violence known today as terrorism. The actual government from President Alvaro Uribe Velez has been developing during his administration, strategies looking for better conditions for those who decide to give away the weapons over the process known as “Reinsercion” or “Reincorporacion” for all the terrorist groups in Colombia. During the investigation, specifically at the work field with the actors from the Reinsercion, through conversations during all the meetings done, where identified the internal and external variables from the surroundings that affected somehow the Reinsercion Process. 85% of the system variables are in the Zone of Conflict, where a big amount of them have some kind of influence over the others, but not all of them are in the zone of the strategic vari ables. This way, there are many front works, important decisions to be taken, awareness on the population to generate, so that all the steps that are to be done toward a solution, reach fruitful results. On the other hand, when analyzing the relation betwe en the actors, the terrorist groups have shown a strong level of convergence from the first moment on the investigation, it could be identify that through the strategic route, this actor confronts the objectives from the other actors of the system. Next, i t will be presented the 4 possible scenarios to happen in the process of Reinsercion in Colombia, and the one with more probability is describe. - Scenario 1: A new Horizon - Scenario 2: Unavoidable Renegotiations - Scenario 3: Everything keeps the same way As the group of experts expressed, this is the scenario with the mayor probability to happen, therefore, as people that have already given up the weapons, perceive the process as a strategy with a lots of difficulties because just a few of the promises that gave the government are really being accomplished. There hasn‟t been a real change in the political structure, and there may be 3 or 4 more governments more and the influence of the narcotrafic could maintain.